Redescription of Bursaphelenchus talonus (Thorne, 1935) Massey, 1956 (Nematoda: Parasitaphelenchidae) and designation of lectotypes - Kaisa, T. R. (Zootaxa, 2003)
Bursaphelenchus talonus is redescribed and a hololectotype and paralectotypes are designated. The species is characterized by three incisures in the lateral field at midbody, an offset head, two rows of cells in the gonad, and a stylet without knobs (11-14 μm). The male body is 654 to 946 μm long with an arcuate tail. A round-ovoid bursa envelops the tail. Three pairs of papillae are present: one pre-cloacal and the other two post-cloacal, near tail terminus. Spicules are 14 to 16 μm long, mitten- shaped, and have a well-developed condylus and rostrum. Distal tips of spicules are pointed and lack a cucullus. The female body is 760 to 836 μm long and tapers posteriorly to a conoid, amucronate tail. The tail terminus is rounded or sub acute. A postuterine sac is present (102-124 μm), and a vulval flap is absent.